2019
DOI: 10.1002/ajpa.23915
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in ethnically diverse high‐altitude native populations: A comparative study

Abstract: Objectives: Andean and Tibetan high-altitude natives exhibit a high concentration of nitric oxide (NO) in the lungs, suggesting that NO plays an adaptive role in offsetting hypobaric hypoxia. We examined the exhaled NO concentration as well as partial pressure of several additional high-altitude native populations in order to examine the possibility that this putative adaptive trait, that is, high exhaled NO, is universal. Methods: We recruited two geographically diverse highland native populations, Tawang Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The evolutionary significance of sex differences in anthropometric and physiological measures is still unclear, as the trend is not comparable across human populations. However, in line with the present study, sex differences in physiological attributes were also reported in previous studies [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The evolutionary significance of sex differences in anthropometric and physiological measures is still unclear, as the trend is not comparable across human populations. However, in line with the present study, sex differences in physiological attributes were also reported in previous studies [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hemoglobin [Hb] concentration was measured from a fingertip blood drop using a Hemocue portable hemoglobin analyzer (Hemocue ® Angelholm, Sweden). Forced vital capacity (FVC) and forced expiratory volume in 1-second (FEV 1 ) were measured on each participant following standard protocols, details given elsewhere [ 17 ]. Spirometry was conducted using a portable spirometer (Care Fusion Micro I Diagnostic Spirometer, USA).…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the influence of altitude in the two studies. Studies assessing the influence of altitude on NO partial pressure indicate that lower NO levels can occur in exhaled air at higher altitudes [23]. The distance between the post-COVID-19 patients and the study carried out in our city is roughly 1900 m.…”
Section: Discussionmentioning
confidence: 91%
“…It was initially identified as the endothelium derived relaxing factor 12,13 . Human studies focusing on high altitude native populations have found higher NO concentration as a major distinguishable characteristic during successful hypoxia adaptive response 14,15 . Previous studies show that lower exhaled NO is characteristic of maladaptive high altitude exposure [16][17][18] and HAPE susceptibility [19][20][21] .…”
Section: Nitrosylation and Carbonylationmentioning
confidence: 99%